2013
DOI: 10.1186/1755-1536-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Direct isolation of myofibroblasts and fibroblasts from bleomycin-injured lungs reveals their functional similarities and differences

Abstract: BackgroundMyofibroblasts play a crucial role in tissue repair. The functional similarities and differences between myofibroblasts and fibroblasts are not fully understood because they have not been separately isolated from a living body. The purpose of this study was to establish a method for the direct isolation of myofibroblasts and fibroblasts from injured lungs by using fluorescence-activated cell sorting and to compare their functions.ResultsWe demonstrated that lineage-specific cell surface markers (lin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 56 publications
6
71
0
Order By: Relevance
“…This definitely remains our focus of future interests. It is also worth noting that IPF fibroblasts are known to be heterogeneous, with cells being at different stages of differentiation (35). We found that IPF fibroblasts with lower PFKFB3 expression demonstrate less differentiation than those with greater PFKFB3 expression (see Figure E1B), suggesting that PFKFB3 promotes myo-Fbs differentiation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This definitely remains our focus of future interests. It is also worth noting that IPF fibroblasts are known to be heterogeneous, with cells being at different stages of differentiation (35). We found that IPF fibroblasts with lower PFKFB3 expression demonstrate less differentiation than those with greater PFKFB3 expression (see Figure E1B), suggesting that PFKFB3 promotes myo-Fbs differentiation.…”
Section: Discussionmentioning
confidence: 72%
“…IPF myo-Fbs are known to be heterogeneous, with cells being at different stages of differentiation (35). To determine the correlation of PFKFB3 expression and TGF-β1 6h con Figure 1.…”
Section: Key Glycolytic Enzymes Are Up-regulated In Lung Myo-fbsmentioning
confidence: 99%
“…While we observed a positive trend in ␣SMA expression in WT-HFD and miR-140 KO mouse SVF cells, primary SVF expression of ␣SMA was not a conclusive indicator of myofibroblast differentiation. Studies from our laboratory and others have established that murine myofibroblasts can be identified using fluorescence-activated cell sorting (FACS) for the markers SCA1 low CD49e high (29). Using these markers, we found that 23.73% of WT-RD mouse SVF cells were myofibroblasts, with an increase to 31.7% in the obese mouse SVF cell population and 48.94% in the miR-140 KO mouse SVF cells (Fig.…”
mentioning
confidence: 82%
“…Lin -Sca-1 + cells, in different organs, seem to overlap with the population of tissue-resident fibroblasts [101][102][103]. In the heart, Sca-1 expression has not been ascribed to a population of cardiac fibroblasts, although the evidence is that Sca-1-expressing cells are present in the myocardial interstitium.…”
Section: Does the Linmentioning
confidence: 99%
“…The latter population expands postbirth and coexpress markers typical of mesenchymal affiliation, that is, PDGFRa, and CD90 [102]. Furthermore, after an injury stimulus, lung fibroblasts (Sca-1 high ) can differentiate into myofibroblasts (Sca-1 low ) and increase the ECM production toward a more efficient repair process [103].…”
Section: Is There a Correlation Of Sca-1 Expression And The Distinct mentioning
confidence: 99%